Lyme Disease in the Era of COVID-19: A Delayed Diagnosis and Risk for Complications - Cheryl B. Novak; Verna M. Scheeler; John N. Aucott (Case Reports in Infectious Diseases)
We describe a patient with fever and myalgia who did not have COVID-19 but instead had Lyme disease. We propose that the co-occurrence of COVID-19 and Lyme disease during the spring of 2020 resulted in a delayed diagnosis of Lyme disease due to COVID-19 pandemic-related changes in healthcare workflow and diagnostic reasoning. This delayed diagnosis of Lyme disease in the patient we describe resulted in disseminated infection and sixth nerve palsy. We present the use of telemedicine to aid in the diagnosis of Lyme disease and to provide prompt access to diagnosis and care during the ongoing COVID-19 pandemic and in the future.